Self-injurious behavior by carotid sinus pressure: case report - Aydın Görücü, Rezzan; Donuk, Tuğba; Yüncü, Zeki; Bildik, Tezan (Journal of Dependence, 2014)
Objective: It has been observed that self-injurious behavior usually starts between 13-19 years of age. Once started, this behavior gains addictive properties and it can be quite difficult for th one to stop it. Manual stimulation of the carotid sinus results in reduced blood pressure, decrease in heart rate and syncope or cardiac arrest may occur. A 15-year-old adolescent girl who has self-injurious behavior by choking will be placed in the present case. Methods: The patient underwent the first psychiatric interview in outpatient clinic and evaluated by youth mental health unit team later. Projective tests, organi-city tests and Self Injurious Behaviour Assessment Inventory were applied to the patient. With the preliminary diagnosis of Adjustment Disorder with Depressed Mood, Attention Deficit and Hyperactivity Disorder and self-injurious behavior, a clinic follow-up arranged with medical treatment. Results: Thematic Apperception Test resulted in anger against family members, aggression and hostile feelings and thoughts, separation individuation difficulties, the feeling of emptiness and loneliness are a result of family break. In the blank card she dreamed herself in the heaven alone and peaceful, as suggesting the risk of suicide. Conclusions: Self-injurious behavior and substance use is observed together in high rates. In this regard close monitoring and security of the case would be appropriate.